Dix ans d’École vus par Jeune Afrique - Bénédicte Kail (Cahiers de la Recherche sur l'Education et les Savoirs)
Through an analyse of the whole bunch of articles dealing with school during the eighties, we’ll show how the weakly newspaper “Jeune Afrique” choose to go with the African states in the democratisation and development of multipartism which has prevailed during these years. Thus, “Jeune Afrique” doesn’t only make few space to that politically sensitive subject, but when it does mention these school and university crisis or reforms, it reduces governments responsibility in emphasizing the economic difficulties which hey have to face.